IC 9407 Automatic Steering Of An Articulated Haul Truck For Underground Mining - J. D. Lane (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The U.S. Bureau of Mines is conducting research on guidance systems for computerized haulage in underground mines. This report describes the process of component selection, installation and testing, perception algorithm development, and steering control algorithm development, to produce a real-time steering control system for an articulated haul truck for underground mining. Ultrasonic transducers were mounted on the truck to provide perception data by measuring the distance to the ribs. Linear potentiometers mounted inside the steering cylinders measured the steering angles. Algorithms, implemented on an inexpensive, robust onboard computer system, analyzed the data and controlled the steering via an electro-hydraulic proportional valve. The steering algorithm presented follows a zone defined by the relative position between the truck and a rib. Experimental verification of the ability to follow the zone in a test corridor on the Colorado School of Mines campus is presented. The automatic steering system successfully negotiated straight sections, curves, and the transition zones between straight and curves with the truck in first and second gears. The resulting real-time automatic-steering system can be applied to many underground articulated machines.